2019
DOI: 10.17511/jopm.2019.i04.06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ziehl-Neelsen Stain versus Fluorescent Microscopy in Diagnosis of Tuberculous Lymphadenitis on FNAC at A Tertiary Care Centre

Abstract: Introduction: Worldwide, TB is one of the top 10 causes of death and the leading cause from a single infectious agent. Lymph nodes tuberculosis is considered the most common form of extrapulmonary tuberculosis and most common cause of lymphadenopathy in developing countries like India.Conventional Ziehl-Neelsen (ZN) method & Fluorescent microscopy (FM) plays an important role for detection of Acid fast bacilli (AFB). Objectives: This study is an attempt to find out cost effective, rapid and sensitive technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a study conducted by Annam et al 6 (2009) out of the 102 lymph nodes evaluated, maximum number of aspirates were from cervical lymph nodes (76/102) followed by inguinal nodes (11/102) and axillary nodes (15/102) Dnyaneshwar et al 7 (2019) revealed the most common site of involvement was cervical region with 27 out of 52 cases (51.92%), followed by supraclavicular region (17.31%) and axillary region (11.53%).…”
Section: Site Of Lymphadenopathymentioning
confidence: 99%
“…In a study conducted by Annam et al 6 (2009) out of the 102 lymph nodes evaluated, maximum number of aspirates were from cervical lymph nodes (76/102) followed by inguinal nodes (11/102) and axillary nodes (15/102) Dnyaneshwar et al 7 (2019) revealed the most common site of involvement was cervical region with 27 out of 52 cases (51.92%), followed by supraclavicular region (17.31%) and axillary region (11.53%).…”
Section: Site Of Lymphadenopathymentioning
confidence: 99%